Trichiasis surgery for trachoma - Merbs, S. (Shannath) (World Health Organization, 2013)
The updated version of this manual combines and updates material contained in three previous manuals on bilamellar tarsal rotation procedure trabut procedure and the final assessment of candidate trichiasis surgeons. This manual is designed to provide specific information for trachomatous trichiasis (TT) trainers who are training others to undertake surgery for entropion trachomatous trichiasis. Other approaches are not addressed. The manual is divided into two parts. The first part covers specifics designed for training TT surgeon candidates and serves as a resource document. The trainer can.